BULLYING BEHAVIOUR AMONG STUDENTS (A REVIEW FOR SCHOOL COUNSELLORS AS A PREVENTIVE MEASURE) - Ibrahim, Muhammad Buchori; Oktaviani, Annisa; Qamara, Nurzayyana; Mujahid, Tamimi; Annastasya, Nadya (Yayasan Amanah Nur Aman, 2025)
The research will unravel the phenomenon of bullying that often occurs by high school students as unconscious perpetrators of bullying. Samples were obtained from several schools, namely several cities in North Sumatra with a total of 760 samples, consisting of students from grades X to XII, consisting of general high schools to boarding school high schools with a total of 6 schools. There are 3 dimensions of bullying behaviour, namely physical, verbal and non-physical/ non-verbal bullying. This research uses quantitative methods with purposive sampling techniques and focuses on high schools that have school counsellors and have made preventive efforts related to the issue of bullying that is rampant. The research instrument used a Likert scale test with a previously validated measuring instrument. Conducting validity and reliability tests and a descriptive approach to describe patterns of bullying behaviour. The results of this study show that there is still bullying behaviour among high school students based on certain grade levels (grade X, XI, and XII), then based on gender. Reports of bullying behaviour still occur with a relatively small portion compared to behaviour that does not involve bullying. Another finding is that there is no significant difference between bullying behaviour patterns in general high schools and boarding schools. However, bullying still occurs in the schools sampled in this research even though they have school counsellors, one of the reasons is that the ratio between school counsellors and students is not balanced so that preventive efforts related to bullying are not optimal.